2017
DOI: 10.1080/02670836.2016.1163876
|View full text |Cite
|
Sign up to set email alerts
|

Low-cyclic fatigue behaviour of an Al–Cu–Mg–Ag alloy under T6 and T840 conditions

Abstract: The low-cyclic fatigue (LCF) behaviour of an AA2139 alloy belonging to the Al-Cu-Mg-Ag system was investigated under T6 and T840 conditions. The T840 treatment involves cold rolling with a 40% reduction prior to ageing, and this was effective in increasing the tensile strength of the alloy. Under cyclic loading at total strain amplitudes (ε ac ) of ±0.4 to ±1.0%, the mechanical behaviour is defined as the prevalence of elastic over plastic deformation processes under both the T6/T840 conditions. The initial we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Al-Cu-Mg-Ag alloys exhibit high specific strength, good fracture toughness and fatigue fracture in addition to superior creep resistance at elevated temperatures. This is attributed to the uniformly dispersed Ω-phase formed during aging as well as its thermal resistance to coarsening [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Cu-Mg-Ag alloys exhibit high specific strength, good fracture toughness and fatigue fracture in addition to superior creep resistance at elevated temperatures. This is attributed to the uniformly dispersed Ω-phase formed during aging as well as its thermal resistance to coarsening [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As the plate thickens during aging, the elastic properties of the plate would be expected to more closely approach those of the bulk [8] and elastic strain fields can be localized in the adjacent Al matrix. Analysis of the edge interfaces may shed light on strain field distributions around the {111} Al plates, knowing of which can help to understand mechanisms of {111} Al plate strengthening in aged aluminum alloys [10,[32][33][34]; preferential Ω-phase orientations observed in the stressaged Al-Cu-Mg-Ag alloys [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible reasons for this may be a decrease in the efficiency of accumulation of the Orowan loops around the inclusion after the cutting [15]. The authors of work [17] observed the softening of AA2139 alloy samples under cycle loading; this softening was explained as a consequence of the repeated cutting of Ω phases. Besides precipitate cutting, accumulation of microvoids is observed in the shear bands that can further initiate the fracture of the deformed sample [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent publications [1,7,8] have focused on investigating the evolution of microstructure and mechanical properties in these alloys.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…Thus, the objective of many researches, recently, is to develop and design new aluminum alloys with precipitates that are stable at high temperatures. The use of Al-Cu-Mg-Ag aluminum alloys (AA2139 and AA2519) has increased substantially in aircraft and military applications due to their low density, exceptional toughness, and moderately high-temperature stability [1][2][3].…”
Section: Introductionmentioning
confidence: 99%